1999
DOI: 10.1021/tx9801864
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Mechanism of Metabolism-Dependent Valproic Acid-Induced in Vitro Cytotoxicity

Abstract: This study was designed to distinguish and evaluate the contribution of reactive metabolite and reactive oxygen species as the mechanism of metabolism-dependent valproic acid-induced in vitro cytotoxicity. The involvement of reactive oxygen species in the mechanism of in vitro cytotoxicity was examined by the addition of a series of antioxidant enzymes and iron chelators to the reaction mixture. Addition of catalase to the reaction mixture resulted in a complete prevention of valproic acid-induced cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 52 publications
5
19
0
Order By: Relevance
“…2A, VPA treatment increased DCF fluorescence in a time-dependent manner, indicating increased ROS production in these cells. The data are consistent with reports in other cell systems that VPA induces the production of ROS (20)(21)(22). Other HDAC inhibitors that are of interest as cancer chemotherapeutic agents, i.e., SAHA (23), MS-275 (24,25), and sodium butyrate (26) have also been reported to increase the production of ROS, although in some cases, ROS production occurred only in transformed cells (25).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…2A, VPA treatment increased DCF fluorescence in a time-dependent manner, indicating increased ROS production in these cells. The data are consistent with reports in other cell systems that VPA induces the production of ROS (20)(21)(22). Other HDAC inhibitors that are of interest as cancer chemotherapeutic agents, i.e., SAHA (23), MS-275 (24,25), and sodium butyrate (26) have also been reported to increase the production of ROS, although in some cases, ROS production occurred only in transformed cells (25).…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, recent reports that VPA induces production of ROS (20)(21)(22) do not explore how the resultant elevated level of ROS influences expression of any gene. Our study clearly provides mechanistic insight into the disposition of VPA-or other HDAC inhibitor-induced ROS production vis-à-vis gene expression; it provides a link between ROS-induced activation of redox-sensitive transcription factors (typified by Nrf2) and their subsequent interaction with the ARE on specific gene promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate that preincubation with PEG-catalase before the administration of valproic acid significantly decreased the production of ROS, although ROS levels did not decrease to baseline levels. In a previous study using in vitro human lymphocyte preparations, catalase significantly protected against valproic acid-induced cytotoxicity; however, similar to findings in the present study, cell death levels were not completely attenuated to baseline levels (Tabatabaei and Abbott, 1999). Given that increased DCF fluorescence can result because of exposure to various ROS and reactive nitrogen species, DCF is considered a general marker for these species (Li et al, 2002).…”
Section: Valproic Acid-induced Homologous Recombination 1307supporting
confidence: 78%
“…For example, previous research has shown that catalase, which detoxifies hydrogen peroxide, prevented valproic acid-induced lymphocyte toxicity and that 1,10-phenanthroline, an iron chelator, also decreased valproic acid-mediated cytotoxicity in vitro (Tabatabaei and Abbott, 1999). These results suggest that the production of hydrogen peroxide and the succeeding iron-catalyzed formation of hydroxyl radicals may be the specific ROS that mediates valproic acid-induced toxicity (Tabatabaei and Abbott, 1999). In addition, valproic acid has been shown to inhibit cardiomyocyte differentiation of embryoid bodies derived from murine pluripotent embryonic stem cells through an increase in ROS (Na et al, 2003).…”
mentioning
confidence: 99%